Effect of Seat Backrest Inclination on the Muscular Pattern and Biomechanical Parameters of the Sit-to-Stand - Tebbache, Nadège; Hamaoui, Alain (Frontiers in Human Neuroscience, 2021)
Objectives: The sit-to-stand (STS) transfer mobilizes an extended part of the kinematic chain throughout a postural phase characterized by trunk flexion and a focal phase consisting of whole-body extension. The aim of this study was to analyze the variations of the global muscular pattern and the biomechanical parameters in both phases, in relation with seat backrest inclination and execution speed. Methods: Fifteen participants were asked to stand up from a seat with 5 backrest inclination settings and at 2 execution speeds. The ground reaction forces and the activity levels of fifteen muscles of the trunk and lower limbs were investigated. Results: Backrest-induced modifications were mainly observed in the postural phase: inclining the backrest backward increased the phase duration and the activity level of the sternocleidomastoideus and the rectus abdominis, while it reduced the activity of the tibialis anterior. It also allowed for an increased maximal anteroposterior velocity of the body center of mass. Higher execution speed led to increased and earlier muscular activities of many trunk and lower limbs muscles, predominantly in the postural phase. Discussion: Taken together, these results suggest that a greater backrest inclination increases the demand in the postural phase due to the increase of the trunk gravity torque and requires an adaptation of muscular activity levels and timing, but with the same overall pattern. The kinetic energy gained during the longer excursion of the trunk may also require less activation of the lower limbs muscles involved in the generation of propulsive forces of the body.